Analisis Skenario Permintaan dan Penyediaan Energi Listrik pada Sistem Interkoneksi Jawa-Madura-Bali 2050 - Rahmat Adiprasetya Al Hasibi; Sasongko Pramono Hadi; Avrin Nur Widiastuti (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
Scenario analysis of electricity supply to meet the demand of electricity is done by the support of LEAP software. Developed LEAP model used the base year of 2010 and the end year of 2050. In the model, scenario consisted of demand and supply side scenarios. In the demand side, designed scenario consisted of the reference and the conservation scenario. The reference scenario used to describe the demand of electricity without any introduction of conservation strategy. While in the conservation scenario, the strategy of energy conservation was integrated in the model. In the supply side, designed scenario consisted of the reference, the optimized, and the reduction of CO2 emission scenario. The reduction of CO2 emission scenario consisted of the implementation of nuclear power plant and renewable energy power plant. The result of the simulation showed that by the implementation of energy conservation strategy the demand of electricity in JAMALI system can be reduced by 20% compare to the reference scenario. The implementation of nuclear power plant can be used to reduce the CO2 emission with the growth of 3.26% per year. In the other hand, the implementation of renewable energy will reduce the CO2 emission with the growth of 3.14% per year.